Winter and Early Spring Herbicides for Kochia Control in Fallow - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in fall of 2015 and spring of 2016 comparing the weed control of several herbicide treatments and their time of application for kochia control in fallow. All herbicide treatments applied in December 2015 provided 99 or 100% kochia control in early spring. However, control declined to less than 60% with these treatments by June 8, 2016. Spring-applied herbicides were generally more efficacious than winter-applied herbicides on June 8, with the best control from treatments of Clarity (dicamba) plus atrazine with or without Zidua (pyroxasulfone) (88 to 89%).
Keywords: Application timing; early preemergence